Bactericidal effect of iron oxide nanoparticles on Staphylococcus aureus - Tran, Nhiem (Dove Medical Press, 2010)
In order to study the effects of iron oxide (IO) nanoparticles on Staphylococcus aureus, IO nanoparticles were synthesized via a novel matrix-mediated method using polyvinyl alcohol (PVA). The IO nanoparticles were characterized by transmission electron microscopy and dynamic light scattering. Further, S. aureus were grown in the presence of three different IO nanoparticle concentrations for four, 12, and 24 hours. Live/dead assays were performed and the results provide evidence that IO/PVA nanoparticles inhibited S. aureus growth at the highest concentration (3 mg/mL) at all time points.